Proceedings of the 15th International Symposium on Open Collaboration 2019
DOI: 10.1145/3306446.3340821
|View full text |Cite
|
Sign up to set email alerts
|

Bringing open data into danish schools and its potential impact on school pupils

Abstract: Private and public institutions are using open and public data to provide better services, which increases the impact of open data on daily life. With the advancement of technology, it becomes also important to equip our younger generation with the essential skills for future challenges. In order to bring up a generation equipped with 21st century skills, open data could facilitate educational processes at school level as an educational resource. Open data could acts as a key resource to enhance the understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…This brief analysis will enable us to identify some of the relevant data categories which will be used as part of specific educational domains. The Open Data review of city enabled us to explore 4 impact domains (educational themes) discussed in [28] with associated sub-domains corresponding to main educational domains, i.e. Mathematics, Science and Geography.…”
Section: Open Data-sets Of Copenhagenmentioning
confidence: 99%
“…This brief analysis will enable us to identify some of the relevant data categories which will be used as part of specific educational domains. The Open Data review of city enabled us to explore 4 impact domains (educational themes) discussed in [28] with associated sub-domains corresponding to main educational domains, i.e. Mathematics, Science and Geography.…”
Section: Open Data-sets Of Copenhagenmentioning
confidence: 99%
“…We also surveyed ten Danish public schools to understand teacher and student perspectives in Open Data usage. This work is discussed in [8] and [30]. Teachers were very positive about the potential to facilitate teaching with actual data, but they required ready-to-use datasets and visualizations as part of teaching assignments.…”
Section: Research Methods and Related Work Regarding Requirementsmentioning
confidence: 99%
“…To develop data skills, the authors suggested designing different activities for data collection as part of learning assignments. In another study, Saddiqa et al [30], identified Open Data domains that could easily facilitate basic school subjects, such as mathematics, science, social science, and geography, and presented example datasets to teachers in interviews and by setting up observations with a group of pupils attempting to make the use of the datasets. The authors highlighted different challenges in using Open Data at the school level.…”
Section: Open Data Usage In Elementary Schoolsmentioning
confidence: 99%
See 2 more Smart Citations